Direct top-quark decay width measurement in the tt¯ lepton+jets channel at √s=8TeV with the ATLAS experiment - Santos, S. P. Amor dos (2018)
This paper presents a direct measurement of the decay width of the top quark using t ¯t events in the lepton+ jets final state. The data sample was collected by the ATLAS detector at the LHC in proton–proton collisions at a centre-of-mass energy of 8 TeV and corresponds to an integrated luminosity of 20.2 fb−1. The decay width of the top quark is measured using a template fit to distributions of kinematic observables associated with the hadronically and semileptonically decaying top quarks. The result, t = 1.76 ± 0.33 (stat.) +0.79 −0.68 (syst.) GeV for a top-quark mass of 172.5 GeV, is consistent with the prediction of the Standard Model.